Histopathological pattern of endometrial samples in abnormal uterine bleeding - R Baral; S Pudasaini (Association of Clinical Pathologists of Nepal, 2011)
Background: Histological characteristics of endometrial biopsy material as assessed by light microscopy remain the diagnostic standard for the clinical diagnosis of endometrial pathology. Management of abnormal uterine bleeding is not complete without tissue diagnosis. The aim of the study was to find out the histopathological pattern of the endometrium in abnormal uterine bleeding. Materials and Methods: Endometrial biopsy specimens received from Jan 2007 to Nov 2010 were studied retrospectively in the Department of Histopathology, Helping Hands Community Hospital, Kathmandu. The specimens were routinely processed and the hematoxyllin and eosin stained slides were studied. Results: A total of 300 specimens were analyzed. In the group of patients less than 40 years of age, 73 (50%) were normal, 34(23%) had abnormal physiologic changes and 13 (9%) had pregnancy related complications and benign changes. In the age group between 40 – 55 years, abnormal physiological changes, benign conditions and normal physiological changes were 45 (32%), 41 (29%) and 37 (26%) respectively. In the age group > 55 years, there were 3(21%) malignant and 3(21%) benign conditions. There were 5(36%) unsatisfactory samples in this age group. Conclusion: It is important to know the histological pattern of the endometrium in abnormal uterine bleeding in different age groups since it will help in the management of the cases. In this study endometrial hyperplasias were seen in 55 cases (18.8%). The importance of studying the histological pattern of endometrium in abnormal uterine bleeding in different age group is to help in correctly managing the cases. Keywords: Endometrium; Simple hyperplasia; Complex hyperplasia; Endometritis; Endometrial Carcinoma. DOI: 10.3126/jpn.v1i1.4443 Journal of Pathology of Nepal (2011) Vol.1, 13-16